Association Between SRC‐1 Gene Polymorphisms and Coronary Artery Aneurysms Formation in Taiwanese Children With Kawasaki Disease - Chen, Yng‐Tay (J Clin Lab Anal, 2014)
BACKGROUND: Kawasaki disease (KD) patients who experience a cardiovascular complication known as a coronary artery aneurysm (CAA) are at high risk of developing ischemic heart disease, which may lead to sudden death. The etiology of CAA in KD patients is unclear, and this study aims to clarify the relationship between steroid receptor coactivator‐1 (SRC‐1) gene polymorphisms and CAA pathogenesis. METHODS: We investigated four SRC‐1 gene polymorphisms (rs11894248, rs17791703, rs7572475, and rs9309308) and their correlation with KD with CAA susceptibility in 327 Taiwanese people (279 KD patients without CAA and 48 KD patients with CAA). RESULTS: The results indicated a statistically significant difference in genotype and allele frequency distributions at the SRC‐1 four single nucleotide polymorphisms (SNPs) between KD patients with and without CAA (P < 0.01). Additionally, Smad3 gene polymorphism (rs12901071) is well known to be associated with KD patients. In our results, Smad3 SNP did not provide a statistically significant difference between KD patients with and without CAA. CONCLUSION: Our data show that SRC‐1 polymorphisms may be the underlying cause of CAA; therefore, the polymorphisms examined in this study warrant further investigation.